Teachers’ Personality Competence in Strengthening Character Education at Muhammadiyah Elementary Schools - Maulidah Hasnah Anas; Rusydi Ananda; Ahmad Syukri Sitorus (Newinera Publisher, 2026)
This study analyzes teachers’ understanding, practices, supporting and inhibiting factors, and the influence of teachers’ personality competence on character education at SD Swasta Muhammadiyah 02 Medan and SDS Muhammadiyah 11 Medan, using a multi-site qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed through data condensation, data presentation, and conclusion drawing. The findings reveal that teachers’ understanding of personality competence is generally good, reflected in their discipline, responsibility, honesty, politeness, and noble character consistently applied in the learning process. Character values are integrated through exemplary speech and actions, including responsibility, discipline, empathy, and cooperation, reinforced by school culture and regular religious activities. Supporting factors include teacher training, regular religious gatherings, and peer support, while obstacles involve limited funding, heavy workloads, suboptimal teacher-parent communication, and diverse student backgrounds. Nevertheless, teachers demonstrate high dedication as role models. Overall, teachers’ personality competence has a significant influence on shaping students’ character, positioning teachers not only as educators but also as strategic agents in personality development at the primary education level.